Supplementation of lysine and probiotics in artificial feed based on local raw materials on feed quality and feed conversion ratio of bileh fish (Rasbora sp.) - Islama, Dini; Diansyah, Sufal; Samuki, Khairul; Vito, Bastian; Febrina, Citra Dina (Universitas Malikussaleh, 2024)
AbstractThis study aims to determine the effect of lysine and probiotic supplementation in artificial feed based on local raw materials on feed quality and feed conversion ratio of bileh fish (Rasbora sp.). This research was carried out from August to September 2023 at the Hatchery and Laboratory of Systems and Technology and the Aquaculture Environment, Faculty of Fisheries and Marine Sciences, Teuku Umar University. In this study, bileh fish measuring 2 - 2.5 cm long were used as test fish. The experimental design used was a non-factorial Completely Randomized Design (CRD) with 4 treatments and 3 replications. The level of treatment applied in feed formulation is feed based on local raw materials as a control (P0), feed based on local raw materials with 1.2% lysine supplementation (P1), 1.4% (P2), 1.6% (P3), 1.8 % (P4) and probiotics 15 ml/kg feed. Feed is given at satiation 3 times a day. The test parameters observed were the quality of the feed produced, daily growth rate and feed conversion ratio of bileh fish (Rasbora sp.). The research results showed that lysine and probiotic supplementation in artificial feed based on local raw materials gave the same response to the quality of the feed produced, but had a significant effect on the daily growth rate and feed conversion ratio of bileh fish. The best daily growth rate and feed conversion ratio were obtained in the P3 treatment.Keywords: Artificial feed based on local raw materials; feed quality; feed conversion ratio; Rasbora sp.